2020
DOI: 10.3390/coatings10080782
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited Biocoatings, Their Properties and Fabrication Technologies: A Review

Abstract: Coatings deposited under an electric field are applied for the surface modification of biomaterials. This review is aimed to characterize the state-of-art in this area with an emphasis on the advantages and disadvantages of used methods, process determinants, and properties of coatings. Over 170 articles, published mainly during the last ten years, were chosen, and reviewed as the most representative. The most recent developments of metallic, ceramic, polymer, and composite electrodeposited coatings are descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 171 publications
(223 reference statements)
0
13
0
Order By: Relevance
“…At higher magnification, the SEM images highlight that the coatings' morphology consists of elongated ribbon-like crystals, very thin, within the nanometric scale, forming a complex morphology that resemble a 3D architecture. All coatings have crystallized perpendicular on the substrate, which is characteristic for the electrochemical deposition process [52].…”
Section: Morphologymentioning
confidence: 99%
“…At higher magnification, the SEM images highlight that the coatings' morphology consists of elongated ribbon-like crystals, very thin, within the nanometric scale, forming a complex morphology that resemble a 3D architecture. All coatings have crystallized perpendicular on the substrate, which is characteristic for the electrochemical deposition process [52].…”
Section: Morphologymentioning
confidence: 99%
“…The critical factor for adhesion is surface roughness. For ceramics that cannot dissociate from ions, their deposition on the metal base is difficult and the obtained surfaces are often non-homogeneous and non-stoichiometric [129].…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…Additionally, comprehensive reviews have been reported on adhesion quality towards bio-metallic substrates 47 , electrical nature of HAp [48][49][50] , heterogeneous organocatalytic aspects of HAp with emphasis on stability and reusability 51 , and a specific review on cationic, anionic, and multi-ionic substitutions of the lattice atoms of HAp 52 . In the field of electrodeposition, a general review of electrodeposited biocoatings 53 and a review focusing on the influence of applied current has been reported 54 . However, there has not been any comprehensive publication exploring the myriad of driving and assisting electrochemical deposition parameters influencing nucleation and crystal orientation with a specific applicative focus on the influence of hexagonal HAp crystal systems towards sensing of various electrolytic and gaseous species.…”
Section: Introductionmentioning
confidence: 99%